Numerical Study of a Micro Gas Turbine Fed by Liquid Fuels: Potentialities and Critical Issues. (December 2015) - Calabria, Raffaela; Chiariello, Fabio; Massoli, Patrizio; Reale, Fabrizio
Abstract: Aim of the paper is to evaluate the potentialities and critical issues of the micro-gas turbine Turbec T100 properly modified in order to be powered by liquid fuels. The main difference with respect to the version designed for gaseous fuels concerns the combustor, namely the combustion chamber and the fuel injection system. The numerical study was carried out using both a 0D matching analysis and a 3D CFD analysis of the combustor. The thermodynamic model, coupled with the operating maps of rotating components, was calibrated using the experimental data collected during operation of the micro-gas turbine with gaseous fuel. The operative parameters computed through the 0D model have been utilized to simulate the behavior of micro-gas turbine fed by liquid fuels, thus obtaining the initial and boundary conditions to be used in the CFD analysis. The combustion process of liquid fuels is analyzed; the main differences at varying loads are discussed in terms of temperature and velocity profiles of the air flows inside the combustion chamber and mean values of turbine inlet temperature and exhaust gaseous concentration. A preliminary study concerning the characteristics of the injection system is also reported.